Human computer interaction research in Web design and evaluation - Zaphiris, Panayiotis; Kurniawan, Sri 1970- (Gale virtual reference library, 2007)
"This is a comprehensive book on Human Computer Interaction and Web design focusing on various areas of research including theories, analysis, design and evaluation. It is not a book on web programming; it provides methods derived from research to help develop more user-friendly websites. It highlights the social and cultural issues in web design for a wider audience"--Provided by publisher.